A compact single layer dual-polarized antenna with wideband operation, high isolation, and high front-to-back ratio for 5G applications - Niamat Hussain; Hung Tran; Dat Tran-Huy; Phuong Kim-Thi (Scientific Reports)
Abstract This paper proposed a simple design of dual-polarized antenna with a single layer and compact structure for 5G applications. The proposed antenna performs several advantages of wideband, high isolation, as well as high front-to-back ratio characteristics. Instead of using complicated feeding network or stacked structure, a directed-fed crossed patch antenna is employed. Noted that by locating the feeding locations close to the center, high isolation can be achieved without requiring any complicated feeding scheme. Additionally, four parasitic patches are introduced to not only enhance the operating bandwidth but also improve the front-to-back ratio. The final antenna with compact overall dimensions of 0.46 $$λ$$ $$×$$ 0.46 $$λ$$ $$×$$ 0.02 $$λ$$ exhibits wideband operation of 7.5% (4.76–5.13 GHz) and high isolation of better than 23 dB. Besides, despite having compact size, the antenna achieves a broadside gain of about 6.0 dB and the front-to-back ratios of around 15 dB across the operating bandwidth.